Malaysians' voices on operation al-Aqsa: a modality analysis of editorial letters - Nor Diyana Saupi,; Mohammad Fadzeli Jaafar,; Maslida Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the use of modality in letters to the editorial in Malaysian newspapers following Operation Al-Aqsa Flood. The operation, carried out by Hamas on October 7, 2023, sparked a significant response from Malaysians, who expressed their opinions through these letters, condemning Israel's retaliatory attacks against Hamas. The use of modality in these letters influences how Malaysians express certainty, obligation, and possibility, shaping their stance and persuasive impact. However, there is limited research on how modality functions in this context, making it essential to analyze it through the lens of Systemic Functional Linguistics (SFL). The study analyzes modality through the lens of Systemic Functional Linguistics (SFL). Its objectives are twofold: (1) to examine the use of modality in letters to the editor in Malaysian newspapers and (2) to explore how the modality system is realized in expressing opinions on the conflict 100 days after Operation Al-Aqsa Flood. The study analyzed 42 letters from the editorial columns of two mainstream Malaysian newspapers, Berita Harian and Utusan Malaysia, using Systemic Functional Linguistics. The findings reveal that the writers employed a total of 324 different modal expressions to articulate their opinions on the conflict. Additionally, the study indicates that the use of modality in these letters depends on the propositions of the sentences. Writers use modality to express judgments and opinions, as well as to persuade readers to take action. They frequently use modal verbs that convey obligation, such as "perlu" (must), "boleh" (can), "akan" (will), "dapat" (can), and "mampu" (able to). This study contributes to a deeper understanding of public sentiment and the linguistic strategies employed in newspaper discourse on geopolitical conflicts.